The study of formation and acid precipitation dynamics as a result of big natural and man-made fires - Кустов, Максим Владимирович (Eastern-European Journal of Enterprise Technologies, 2016)
In the event of big natural and man-made fires, many hazardous chemicals are released into the environment. These compounds react with the atmospheric components to form sulfuric and nitric acids. Among the atmospheric components, highly active radicals - hydroxyl, hydroperoxide and nitrate ions have the greatest influence on the acid formation processes. The reaction of acids with atmospheric water leads to acid precipitation. The paper discusses the physical and chemical features of the transformation of gaseous combustion products into acidic products. Using the kinetic multilayer model of gas particles, the absorption dynamics of gas-phase nitric and sulfuric acids by water microdroplets in the atmosphere is considered. Further evolution of acid solution microdroplets occurs due to coagulation. The coagulation rate significantly depends on the relative sizes of droplets. The criterion is the Knudsen number, which determines the flow of Brownian or gravity coagulation. The motion of small droplets is determined by the interaction with heat molecules and the absence of sedimentation. As for relatively large droplets, interaction with heat molecules can be neglected. They settle in the air stream due to weight and absorb small droplets when colliding. The intensity of the coagulation growth of droplets in the course of precipitation is determined using the mathematical simulation.